Designing Products Sports Shoes Using the Quality Function Deployment (QFD) Method - Ribangun Bamban Jakaria; Hadi Purnomo; Iswanto (Universitas Muhammadiyah Sidoarjo, 2021)
Sports shoe products produced by (MSME) actors in Mojokerto have not demonstrated theperformance of products received by the public, this is based on the design of shoes done still sourced from thedesign of sports shoes owned by well-known brands that are marketed around mojokerto, research is done todayaimed to design competitive sports shoe products, with the best quality as well as with the latest models that suitthe needs of consumers. The design of sports shoe products is carried out today using Quality FunctionDeployment (QFD). The result of the design of shoe products that are ed has product specifications namelytopline / collar made of elastic and soft, eyestay/strap hole with a certain amount, patterned and embossed upper,flexible and soft midsole, toe box with hole point as air circulation, lace shoe adjusted to skin color, logo designused embossed, detachable insole and elastic insole, flexible wedge, jagged outersole, elastic tongue/tongue,patterned vamp toe, soft and soft tab heel. With the design of the shoes is expected to provide a shoe design thatis acceptable to the public, has competitiveness and reduces the reliance of shoe design on famous brands